Opportunities and challenges through water management in the fluvial landscape of the Lower Lacantún River basin, Chiapas, Mexico - Schroder, Whittaker (2025)
Introduction: The Maya lowlands of the Yucatán peninsula are characterized by karst topography where most water is accessed through subterranean sources. Nevertheless, some Maya communities occupied riverine environments that offered opportunities for resource acquisition, navigation, and long-distance trade. Objectives: In the region of the Lower Lacantún River basin near the confluence with the Usumacinta River, at the modern boundary between Mexico and Guatemala, the fluvial landscape presented such opportunities to Maya communities, alongside the challenges associated with extreme flooding near the alluvial plain. Seasonal, short-term risks included the destruction of crops along river margins, while long-term risks of extreme flooding represented threats to settlements. The current study investigates the role that indigenous knowledge can play in the research area, as documented in the archaeological landscape through the form of past water management, for land use and urban planning today. Methods: Through reconnaissance, survey, excavation, and remote sensing, alongside descendant communities, this project has identified and investigated archaeological features designed for water retention and drainage, within and outside of urban centers. [Continue reading in article]